2012
DOI: 10.1177/109804821201600106
|View full text |Cite
|
Sign up to set email alerts
|

A Personal Branding Assignment Using Social Media

Abstract: The advertising industry has changed dramatically in the last few years with increasing percentages of marketing expenditures transferring from traditional channels to emerging digital and social channels. Educators need to recognize the changing needs of the marketplace and provide appropriate education to students to prepare them for this exciting new advertising environment. Recent changes to Google search results now incorporate social elements from Google + and other Google properties, introducing the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 3 publications
3
24
0
4
Order By: Relevance
“…According to the results, the skill component has a significant positive effect on the personal brand image of Taekwondo elite players. This finding is consistent with the study results of (16,17,19,20,24). Andrew and Jackson (2013) stated that, in general, the image reflected by players is largely based on their individual skill, agility and creativity (16).…”
Section: Discussionsupporting
confidence: 88%
“…According to the results, the skill component has a significant positive effect on the personal brand image of Taekwondo elite players. This finding is consistent with the study results of (16,17,19,20,24). Andrew and Jackson (2013) stated that, in general, the image reflected by players is largely based on their individual skill, agility and creativity (16).…”
Section: Discussionsupporting
confidence: 88%
“…The issue of the curricula for personal branding and the practical challenge of preparing people to be effective personal branders were raised as early as 2005 in academic sources (Shepherd, 2005 ). Out of the 100 reviewed articles, 11 deal with teaching personal branding, suggesting various curricula (Edmiston, 2014 ; Johnson, 2017 ) and estimating effectiveness of different assignments in teaching personal branding skills (McCorkle and McCorkle, 2012 ; Wetsch, 2012 ; Stanton and Stanton, 2013 ; Jones and Leverenz, 2017 ). This review demonstrated that there is limited understanding and concurrence on the concepts and processes; therefore teaching unproven ideas raises ethical issues in itself.…”
Section: Resultsmentioning
confidence: 99%
“…Z tego powodu publikacje z tej tematyki niejednokrotnie są bardzo ogólne i nie powiązane z dorobkiem nauk o organizacji, a szczególnie z dorobkiem marketingu w obszarze zarządzania marką. Chociaż powoli personal branding "przenosi" się" do świata akademickiego (przedmiot o takim tytule wykładany jest na kursie MBA w jednym z kanadyjskich uniwersytetów [Wetsch 2012]; w Polsce krakowska AGH uruchomiła pierwsze studia podyplomowe poświęcone profesjonalnemu kształtowa-niu wizerunku osobistego), to nadal brakuje jednak wystarczająco rzetelnych, teoretycznych i empirycznych analiz z tego zakresu.…”
Section: Zakończenieunclassified